Farmer experimentation for climate adaptation with triadic comparisons of technologies (tricot): a methodological guide - Steinke, J.; Etten, Jacob van (2016)
Triadic Comparisons of Technologies (tricot), is a new approach to test crop varieties and other technologies on-farm, under realistic conditions. Through simple and hands-on experimentation, the participating farmers identify innovations that will be of real benefit to them. Tricot is a ready-made methodology, serving both research, and the dissemination of varieties and other technologies and practices in highly variable areas. Through geographically distributed testing, tricot is able to provide information about geographic patterns in climate adaptation and help to speed up the identification of locally suitable technologies to respond to climate change. It provides a means to linktechnology development of research institutes to real-life experiences of farmers. It is supported by a digital platform that can be found at www.climmob.net. This publication provides a description of the methodology with guidelines for its implementation in the field.